Influence of agro-climatic conditions on chemical compositions and repellency effect of Mentha longifolia plant against malaria vector, Anopheles stephensi. (2nd January 2023) - Pirmohammadi, Masoumeh; Abai, Mohammad Reza; Shayeghi, Mansoureh; Vatandoost, Hassan; Rahimi, Sara; Pirmohammadi, Maryam
Abstract: Medicinal plants are used as control measure against mosquito bites. Efficacy, protection time and the effective dose of specimens were assessed on Anopheles stephensi . The malaria vector were reared under insectary condition, plants were collected from different parts of the country and identified and certified based on the morphological characters. The chemical composition of the volatile constituents was evaluated by gas chromatography–mass spectrometry (GC-MS). The repellent activity of extracted essential oils was evaluated against adult female An. stephensi by using the animal-bait technique on white rabbits ( Oryctolagus cuniculus ). Major component of the essential oils from each area according to climatic conditions indicated 36 compounds in M. longifolia, Cis-β-guaiene 42%, Cubenol 22%, and (Z)-3-hexenol 11.2% in Armand district, as well as 13 compounds with 8-cedren-13-ol 85.5%, Cis-ascaridole 4.2%, and Oplopanone 3% in Shah-manzar were the major components of the essential oil at autumn season. Mean protection time and the efficacy of specimens from different climates were 5.9, 6.6 and 2.3, 3.1 and 2.3, 3.3 and 3.0, 3.3 h, respectively. ED50 and ED90 values for the same specimens were calculated 1.48, 10.46, and 2.94, 24.02, and 5.26, 31.83, and 13.68, 84.23 μl/cm 2, respectively. A total of 65, 11, 29, and 24 chemical compounds were isolated. Humid temperate cold area had the highest protection time. It can be considered as an appropriate herbal repellent against malaria vector.